Goal-Directed Fluid Therapy Using Stroke Volume Variation Does Not Result in Pulmonary Fluid Overload in Thoracic Surgery Requiring One-Lung Ventilation. (21st June 2012) - Haas, Sebastian; Eichhorn, Volker; Hasbach, Ted; Trepte, Constantin; Kutup, Asad; Goetz, Alwin E.; Reuter, Daniel A.
Abstract : Background . Goal-directed fluid therapy (GDT) guided by functional parameters of preload, such as stroke volume variation (SVV), seems to optimize hemodynamics and possibly improves clinical outcome. However, this strategy is believed to be rather fluid aggressive, and, furthermore, during surgery requiring thoracotomy, the ability of SVV to predict volume responsiveness has raised some controversy. So far it is not known whether GDT is associated with pulmonary fluid overload and a deleterious reduction in pulmonary function in thoracic surgery requiring one-lung-ventilation (OLV). Therefore, we assessed the perioperative course of extravascular lung water index (EVLWI) and p a O 2 / F i O 2 -ratio during and after thoracic surgery requiring lateral thoracotomy and OLV to evaluate the hypothesis that fluid therapy guided by SVV results in pulmonary fluid overload. Methods . A total of 27 patients (group T) were enrolled in this prospective study with 11 patients undergoing lung surgery (group L) and 16 patients undergoing esophagectomy (group E). Goal-directed fluid management was guided by SVV (SVV < 10%). Measurements were performed directly after induction of anesthesia (baseline—BL), 15 minutes after implementation OLV (OLVimpl15), and 15 minutes after termination of OLV (OLVterm15). In addition, postoperative measurements were performed at 6 (6postop), 12 (12postop), and 24 (24postop) hours after surgery. EVLWI was measured at all predefined steps. The p a O 2 / F i O 2 -ratio was determined at each point during mechanical ventilation (group L: BL-OLVterm15; group E: BL-24postop). Results . In all patients (group T), there was no significant change ( P > 0.05 ) in EVLWI during the observation period (BL: 7.8 ± 2.5, 24postop: 8.1 ± 2.4 mL/kg). A subgroup analysis for group L and group E also did not reveal significant changes of EVLWI. The p a O 2 / F i O 2 -ratio decreased significantly during the observation period (group L: BL: 462 ± 140, OLVterm15: 338 ± 112 mmHg; group E: BL: 389 ± 101, 24postop: 303 ± 74 mmHg) but remained >300 mmHg except during OLV. Conclusions . SVV-guided fluid management in thoracic surgery requiring lateral thoracotomy and one-lung ventilation does not result in pulmonary fluid overload. Although oxygenation was reduced, pulmonary function remained within a clinically acceptable range.